Marketing information and library services - Especialistas, Los (2000)
Forum of specialists oriented towards the marketing of information and services in libraries with two approaches: On the one hand, the need to professionalize the task of the market of information products and services and, on the other, the need not to fall into the traps of fashions and to misunderstand the main role which is administration as a social good.